A rethinking of children at stake. Musings for their revaluation - París, Sonia; Haynes, Joanna (Araucaria, 2020)
A rethinking of children is necessary, particularly in Western societies, where a Modern conception has prevailed, based on ideas of children’s fragility, vulnerability and dependence on adults. This Modern conception has emphasized the notion of life as a process divided into identificable stages and has considered age as the main criterion to identify what it is to be a child and an adult. In front of this conception, this text proposes the objective of recuperating the alternatives offered by both Postmodern theory and Posthumanism, in order to propose a revaluation of children as empowered creative subjects, who, in dialogue to adults and in relation with more-than-humans (animals and things), will be understood as co-educators. To that end, pedagogies that give priority to children’s creativity and to their critical and ethical thinking will be emphasized, making particular connection to the school of Philosophy with Children and the methodology based on picturebooks.